Design and Development of a Model for Managing Organizational Behavior of Difficult Employees - Sayyid Hasan, Mohammed; Dalvi, Mohammad Reza; Abdulhasan Jasim, Faez; Hadi Pikani, Mehraban (Management Strategies and Engineering Sciences, 2025)
The aim of this research is to design and develop a model for managing the organizational behavior of difficult employees. This study is applied-developmental in terms of its objective and descriptive-survey in terms of methodology. The research approach is an exploratory mixed method, combining qualitative and quantitative techniques. In the qualitative section, Strauss and Corbin’s grounded theory technique (2007) was utilized, while structural equation modeling (SEM) was employed in the quantitative section. The qualitative population consisted of educational experts (managers and academic experts at the University of Misan, Iraq), and 16 individuals were selected as the sample using purposive sampling. Semi-structured interviews were conducted to gather expert opinions, and the grounded theory model was analyzed using ATLAS.ti software. In the quantitative section, the population consisted of employees at the University of Misan, with a total of 200 members. Based on Morgan’s sampling table, 132 individuals were selected as the sample. The data collection tool for the quantitative phase was a researcher-developed questionnaire utilizing a five-point Likert scale. The content validity of the questionnaire was confirmed by consulting experts and specialists, and its reliability was verified by calculating Cronbach’s alpha coefficient. The collected data were analyzed using AMOS software to estimate the structural equation model. The findings revealed 20 general categories within a paradigmatic model, including causal conditions (negative organizational behaviors, negative managerial behaviors, factors causing difficult behavior, organizational damages), central phenomenon (managing difficult employees), contextual conditions (negative organizational culture, negative communications, improper organizational changes, inefficient leadership), intervening conditions (flawed policies and procedures, unsuitable work environment), strategies (designing a human resource management model, formulating organizational policies and regulations, effectively managing difficult employees, providing psychological and social support), and outcomes (a healthier and more efficient workplace, cultural improvement, enhanced organizational performance, effective human resource management, and reduced difficult behaviors).